Schools as Differential Environments for Students’ Development: How Tracking and School Composition Affect Students’ Transition After the End of Compulsory Education - Scharenberg Katja; Rollett Wolfram (Swiss Journal of Sociology, 2023)
Tracking leads to differential developmental environments resulting in educational inequalities. We investigated whether tracking and school composition affect students’ transition to post-compulsory education. Based on data of two Swiss school-leavers’ cohorts (2000/2016), multilevel analyses show that the social and achievement-related school composition and track affiliation predict transitions beyond students’ individual characteristics. Compositional effects were in part differentially predictive depending on students’ track affiliation.